2017
DOI: 10.1002/adma.201605197
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and Local Structure of LaNiO3 Thin Films

Abstract: approaches to controlling the MIT have been made, for example, by electric field effects [9] and through optical means. [10] Today, RNOs retain a strong focus, with recent work striving to understand their physics. [11][12][13][14][15] The R = La compound is the only RNO that does not have an MIT in bulk; it is metallic and paramagnetic at all temperatures. LaNiO 3 (LNO) may prove an ideal candidate as a base for engineering functional oxide heterostructures. For instance, it was suggested that specially engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 40 publications
9
50
0
Order By: Relevance
“…Over the entire field range, the Hall response is essentially linear with non-discernible higher-order terms, which supports a dominant single-band in transport. The sign of the Hall coefficient R H is positive suggesting predominantly hole-like charge carriers, in agreement with previous studies 11,31 . Despite the fact that LNO is a metal, we observed an increase in R H by about a factor of three upon cooling, which is shown in Figs.…”
supporting
confidence: 92%
“…Over the entire field range, the Hall response is essentially linear with non-discernible higher-order terms, which supports a dominant single-band in transport. The sign of the Hall coefficient R H is positive suggesting predominantly hole-like charge carriers, in agreement with previous studies 11,31 . Despite the fact that LNO is a metal, we observed an increase in R H by about a factor of three upon cooling, which is shown in Figs.…”
supporting
confidence: 92%
“…LaNiO 3 seems less affected by these limitations with the exception of the formation of cracks at very large thickness (> 300 nm), and therefore appears to be a versatile electrode material. However, the conductive properties of LaNiO 3 can be altered in ultrathin epitaxial films, as previously discussed 240,241 . Finally, we note that LaNiO 3 has the added advantage that it is inexpensive compared to other oxides such as SrRuO 3 .…”
Section: Exploiting the Conductivity Of Laniomentioning
confidence: 75%
“…38 This behavior may have a largely structural origin. Hardening of the phonon modes associated with oxygen octahedral distortions, concomitant with the dimensionality-induced electronic localization, has recently been reported 143 . In the same study it was found that the film structure differentiates into three different local structures -one found on the surface, one towards the interface with the substrate and the third in the interior layers where the boundary effects are minimal.…”
Section: The Case Of Lanio 3 Thin Filmsmentioning
confidence: 92%
“…Such a symmetry misfit is typical for the epitaxy of orthorhombic perovskites on square surfaces of versatile substrates [10][11][12][13]. The symmetry misfit relaxes within a few nanometers near the film-substrate interface, as was evidenced by the evolution of tilts towards bulklike patterns in nickelates [11,[14][15][16].…”
Section: A Film Structurementioning
confidence: 92%